The Effect of Plyometrics Training and Leg Length on Leg Muscle Power in Female Volleyball Athletes, District. Rembang 2023 - Wicaksana, Pungky Wicaksana Putra; Nasuka, Nasuka; Rahadjo, Hermawan Pamot (Journal of Physical Education and Sports, 2024)
Abstract ___________________________________________________________________ Physical conditions influence an athlete's performance to achieve achievements. The problems that are often encountered are that athletes tend to get bored when doing strength training separately and there is a lack of variety in training. Therefore, variations are carried out by combining several training models. This study aims to determine and analyze the effect of plyometrics training and leg length on leg muscle power in female volleyball athletes in Rembang Regency. This research method uses quantitative methods with experimental methods. The sample used was 24 athletes who took part in the PORPROV selection for women's volleyball in the District. Rembang. This research instrument uses tests and measurements with the vertical jump test. Data analysis used the two way anova test. The results of the research stated that there was an effect of plyometric box drill and plyometric standing jump training on increasing leg muscle power abilities in female volleyball athletes in Rembang Regency. There is an influence of high and low leg length on increasing the ability of leg muscle power in female volleyball athletes in Rembang Regency. The effectiveness of plyometric box drill, plyometric standing jump and high and low leg length training in increasing leg muscle power in female volleyball athletes in Rembang Regency shows the same level of effectiveness.